A NEW REGIONAL PETROLEUM SYSTEMS MODEL FOR CENTRAL ITALY AND THE CENTRAL ADRIATIC SEA SUPPORTED BY BASIN MODELLING AND AN ANALYSIS OF HYDROCARBON OCCURRENCES. (29th September 2021) - Lipparini, Lorenzo; D'Ambrosio, Andrea; Trippetta, Fabio; Bigi, Sabina; Derks, Jan Federik; Bambridge, Victoire Roblet; Cassola, Teodoro
Abstract : The petroleum system in Central Italy and the Adriatic Sea is of great interest for future hydrocarbon exploration. However, major uncertainties remain about key risk elements such as source rock spatial distribution and maturation history, the timing of hydrocarbon migration, and the nature of migration pathways. This paper presents a new regional‐scale petroleum systems model based on an integrated inter‐disciplinary study which includes public‐domain subsurface data on key petroleum systems elements, heat‐flow and petroleum geochemical data, and an extensive set of 1D basin models. Results show the importance of the Mesozoic palaeogeographic and stratigraphic setting which was characterized by the presence of platform and basinal domains. Thermal data highlight an overall higher basal heat flow in platform domains which persist at the present‐day. Considering the geochemical and thermal characteristics of possible source rocks in the study area, the Upper Triassic Burano Formation appears to be the most likely active source rock but only in those geological domains where it has been deeply buried. In particular, source rocks reached maturity only during the most recent Apennine deformation phase in the late Pliocene/early Pleistocene, i.e. after the deposition of regional seals such as the Messinian Gessoso‐Solfifera Formation. Lateral migration is suggested to have occurred to explain most of the known oil accumulations. The margin of the Apulia Platform could have acted as a migration pathway for hydrocarbons, connecting basinal kitchens to the carbonate reservoir units at the top of the platform succession within which oil and gas accumulations have been proven. Heavy oils could represent early expulsion products from the source rock, but may also locally be a result of biodegradation due to recent partial exhumation of the traps and the loss of lighter components. The results of this study may support ongoing and future exploration efforts over other carbonate platforms in the study area, and more widely on carbonate targets elsewhere in the Mediterranean region.